Northeast of Lithuania partisan region: organizational activity, connections, leaders - Vaičiūnas, Gintaras (Genocidas ir rezistencija, 2024)
In 1947–1952, most of the partisan units of Aukštaitija were united by the Northeastern Lithuania Partisan Area (other names – King Mindaugas, Mountains, Eastern). The regional headquarters led the partisan struggle in Aukštaitija, maintained contacts with the Lithuanian partisan high command, and published periodicals. The Lithuanian partisans’ struggle for independence was manifested in organisational, social and military activities. Based mainly on archival documents, the article examines the organisational activities of the Northeastern Lithuanian Partisan Area, the changes in its subordination, structure and territory, sheds light on the most important events of its history, and shows the place of the area in the overall Lithuanian partisan organisation.
Keywords: Soviet occupation; armed resistance; partisans; partisan structure; partisan leaders